2013
DOI: 10.1111/adj.12103
|View full text |Cite
|
Sign up to set email alerts
|

The role of oral soft tissues in swallowing function: what can tongue pressure tell us?

Abstract: Tongue pressure data taken from healthy subjects during normal oral activities such as mastication, speech and swallowing are providing us with new ways of understanding the role of the tongue in craniofacial growth and function. It has long been recognized that the sequential contact between the tongue and the palate plays a crucial role in the oropharyngeal phase of swallowing. However, because the focus of most research on intraoral pressure has been on the generation of positive pressure by the tongue on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 68 publications
(68 reference statements)
0
19
0
5
Order By: Relevance
“…The lateral borders of the tongue lie at rest on the occlusal surfaces of the lower first molars and in speech for "tooth sounds" the tongue is in contact with the palatal aspect of the maxillary anterior teeth. Swallowing is initiated by the tip of the tongue being forced on to the palatal aspect of the upper incisors and remaining in this area during the entire swallow, pressures of 80g/cm 2 being exerted, which is 20 times as great on the teeth as pressures recorded at rest, 4g,cm 2 [18,20]. seconds for the duration of tongue licking was chosen in line with previous research by Vieira et al [14] and Gregg et al [13] who applied a similar regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral borders of the tongue lie at rest on the occlusal surfaces of the lower first molars and in speech for "tooth sounds" the tongue is in contact with the palatal aspect of the maxillary anterior teeth. Swallowing is initiated by the tip of the tongue being forced on to the palatal aspect of the upper incisors and remaining in this area during the entire swallow, pressures of 80g/cm 2 being exerted, which is 20 times as great on the teeth as pressures recorded at rest, 4g,cm 2 [18,20]. seconds for the duration of tongue licking was chosen in line with previous research by Vieira et al [14] and Gregg et al [13] who applied a similar regimen.…”
Section: Discussionmentioning
confidence: 99%
“…[1618] Suprahyoid and floor of mouth musculature are critical for protecting the airway by preventing aspiration and penetration since they elevate the hyoid and larynx to allow for appropriate bolus diversion away from the airway and help to open the esophagus for bolus entry. [19] Many studies have reported strong correlations between dysphagia and the radiation dose to the pharyngeal constrictors.…”
Section: Introductionmentioning
confidence: 99%
“…[15, 20] During deglutition, the soft palate functions to both prevent premature entry of the bolus into the unprepared pharynx and to provide a velopharyngeal seal to allow distal driving pressure during pharyngeal transit. [18] While the effects of RAD on the soft palate have not been studied as extensively as those on the superior pharyngeal constrictor, it typically receives a large dose of radiation in the treatment of NPC and is a logical organ-at-risk to study.…”
Section: Introductionmentioning
confidence: 99%
“…Na mastigação, tem o papel de auxiliar a coletar e posicionar o alimento nas faces oclusais (FELÍCIO, 2004). Durante a deglutição tem o papel de impulsionar o alimento para a faringe, pois suas características estruturais lhe permitem exercer movimentos para selar o conteúdo do bolo anteriormente e lateralmente e gerar pressão para a propulsão posterior do bolo KIESER, 2014;TANIGUSHI et al, 2008). A anatomia e fisiologia da língua humana é mais complexa do que a de outras espécies, sendo claro que a língua humana executa movimentos exclusivos durante a deglutição e fala, porém muitas de suas especificações anatômicas ainda são desconhecidas (MU;SANDERS, 2010;SANDERS et al, 2013).…”
Section: A Língua E Seu Desempenhounclassified
“…Suas características estruturais lhe permitem exercer movimentos para selar o conteúdo do bolo, anteriormente e lateralmente, e gerar pressão para a propulsão posterior do bolo KIESER, 2014;TANIGUSHI et al, 2008). Na mastigação, a língua realiza a manipulação e transporte do alimento para as faces oclusais (FELÍCIO, 2004) e na fala, tem ação na articulação dos fonemas (MU; SANDERS, 2010;SANDERS et al, 2013).…”
Section: Introductionunclassified